Mexico - Berg, Elizabeth (Milwaukee : G. Stevens, 1997)
Describes the background and customs associated with some of the important fiestas celebrated in Mexico.
8 - 10 years
Keywords: Festivals -- Juvenile literature. -- Mexico; Festivals -- Mexico; Holidays -- Mexico; Mexico -- Social life and customs -- Juvenile literature; Mexico -- Social life and customs